2013
DOI: 10.1089/vim.2012.0054
|View full text |Cite
|
Sign up to set email alerts
|

IK Induced by Coxsackievirus B3 Infection Transiently Downregulates Expression of MHC Class II Through Increasing cAMP

Abstract: Major histocompatibility complex (MHC) class II expression is critical for the presentation of antigens in the immune response to viral infection. Consequently, some viruses regulate the MHC class II-mediated presentation of viral antigens as a mechanism of immune escape. In this study, we found that Coxsackievirus B3 (CVB3) infection transiently increased IK expression, which reduced the expression of MHC class II (I-A/I-E) on splenic B cells. Interestingly, CVB3-induced IK elevated cAMP, a downstream molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…To investigate the potential of tIK cytokine in RA, we generated a crossbred mouse by breeding a tIK-expressing transgenic (termed tIK-Tg) mouse12 and an IL-1 receptor antagonist knockout (termed IL1RaKO) mouse on the BALB/c background131415. This crossbred mouse was designated tIK-IL1RaKO (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate the potential of tIK cytokine in RA, we generated a crossbred mouse by breeding a tIK-expressing transgenic (termed tIK-Tg) mouse12 and an IL-1 receptor antagonist knockout (termed IL1RaKO) mouse on the BALB/c background131415. This crossbred mouse was designated tIK-IL1RaKO (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…tIK transgenic mice were generated as previously described12. IL-1 receptor antagonist knockout (IL1RaKO) mice on the BALB/c background were kindly provided by M. L. Cho (Catholic Research Institute of Medical Science, The Catholic University of Korea, Korea).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we reported that Coxsackievirus B3 (CVB3) infection transiently induced IK mRNA and that the expressed IK protein bound to G protein-coupled receptors and increased cyclic AMP (cAMP) levels in cytoplasm, and that this CVB3-IK-cAMP axis was the cellular mechanism behind the previous observation that CVB3 infection reduced MHC class II expression in myocytes [ 5 ]. Therefore, induction of IK might be a survival strategy of CVB3 to escape host immune responses [ 6 ].…”
Section: Introductionmentioning
confidence: 99%